2014
DOI: 10.1080/15438627.2014.915835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Ankle Proprioception in Adult Women during 16 Weeks of Training and Eight Weeks of Detraining

Abstract: This study evaluates the effects of training and detraining on ankle proprioception in terms of kinesthesia in adult women. Sixty participants were randomly assigned to three groups. Tai Chi and Brisk Walking Groups went through a 16-week training period followed by an eight-week detraining period. The ankle plantar-flexion, dorsal-flexion, inversion, and eversion kinesthesia were measured every four weeks. The ankle kinesthesia in plantar/dorsal flexion of both exercise groups decreased, but the Tai Chi Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Similarly, another study also corroborated that a 10-week TC training could decrease the COP path and area during postural control tests in the older adults 12 . Furthermore, TC exercise could improve joint kinesthesia, 13 muscle strength in lower extremities, 14 and neuromuscular reaction in older women 15 …”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, another study also corroborated that a 10-week TC training could decrease the COP path and area during postural control tests in the older adults 12 . Furthermore, TC exercise could improve joint kinesthesia, 13 muscle strength in lower extremities, 14 and neuromuscular reaction in older women 15 …”
Section: Introductionmentioning
confidence: 60%
“…Some older people have stopped training for various reasons, including diseases, injuries, and travels, and they may go on retraining. After post-exercise, some intervention effects on the physical function could start to diminish 13 . Nevertheless, few data offered the magnitude and retention of the maintenance of postural control ability during detraining periods.…”
Section: Introductionmentioning
confidence: 99%
“…15 The increament of balance, if it is based on this previous study, should be similar between the two groups. 15 The recent study found no difference in increament of strength between the two groups.…”
Section: Discussionmentioning
confidence: 80%
“…However, in another study, Tai Chi and brisk walking intervention both increase the proprioception of the participants. 15 The result is even greater in Brisk Walking group. 15 The increament of balance, if it is based on this previous study, should be similar between the two groups.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies indicated that Tai Chi Chuan exercise effectively improved ankle kinesthesia (Zhang, Sun, Yu, Song, & Mao, 2015) and may reduce the risk of falls among older adults (Low, Ang, Goh, & Chew, 2009;Li, Harmer, Fisher, & Mcauley, 2004;Li et al, 2005;Ramachandran, Rosengren, Yang, & Hsiao-Wecksler, 2007). Although Tai Chi Chuan exercise is considered to be a suitable exercise to reduce the risks of falls for older adults, the direct effect on obstacle crossing has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%